Musicera för och musicera med: – om flytande gränser och skiftande roller i utövandesituationer - Åkesson, Ingrid (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2013)
The basic point of departure for this article is a view of music characterized by more emphasis on the process, and on music as a widespread human resource and activity, than on music as a product created by the few for the consumption of the many. The article combines some principal discussion with empirical examples. I have studied musical situations that consist of small festivals and workshops dedicated to traditional singing in Sweden and Scotland. These events are analysed from the perspective of a number of fields or continua, such as presentative versus participatory music-making (Turino 2008), professional versus amateur, artist versus audience, and communication as one-way versus multidirectional. Focus is placed on the fluidity, overlapping and dynamics concerning the participants' musical and social roles and functions within these musical events. The text is based on the project Music for listening or music for doing at the Department of Culture and Media studies at the of Umeå University, which I conducted 2010–12.